What do mathematics lessons look like? Analyses of primary students’ drawings - Rott, Benjamin; Barton, Laura; Hatisaru, Vesife (Frontiers in Psychology, 2023)
Analyzing and interpreting drawings of students to assess their experiences and beliefs has become a fairly often used research method-especially when focusing on young students who cannot easily be asked via self-report questionnaires. However, such methods still need to be discussed and analyzed regarding their objectivity and validity. In this study, we elaborate on a drawing-based instrument (Draw A Mathematics Classroom Test), asking 104 fourth-grade students to each draw a picture of their usual mathematics lessons. We especially focus on developing and validating coding of the data with low-inferent categories, that is well-operationalizable categories that can be used with high interrater-reliability like the presence of teachers, the arrangement of students' desks, and/or teacherstudents communication. The results confirm the reliability and validity of the methodological approach (e.g., pictures in which the teacher is drawn larger than the students also depict them in the center and show students working alone). The students' drawings suggest that almost half of the participating students perceive their lessons as teacher-centered.